The effect of applied load and sliding speed on the tribological properties of Nylon 6 and ultra-high-molecular-weight polyethylene. Issue 3 (8th April 2014) - Unal, Huseyin; Hakan Yetgin, Salih; Findik, Fehim
Abstract : Purpose: – The purpose of the study was to find the best performance polymer material to be used in railway car bogies. Design/methodology/approach: – Wear tests and optical and scanning electron microscopy were used. Findings: – The friction coefficients of ultra-high-molecular-weight polyethylene (UHMWPE) and Nylon 6 polymers, as opposed to AISI 4140 steel, reduced with the increment of applied loads. With the increment of sliding speed, the friction coefficient increased in both UHMWPE and Nylon 6 polymers. The specific wear rate of the UHMWPE polymer was determined to be about 10-14 m2/N, whereas the rate of Nylon 6 was determined to be 10-13 m2/N. Practical implications: – The aim of the study was to find the best performance polymer material to be used in railway car bogies. Originality/value: – The friction and wear performance of UHMWPE and Nylon 6 engineering polymers were studied and compared to their AISI 4140 steel counterparts. It is an original work and it is not published in any media.